Prenatal Exposure to a Climate-Related Disaster Results in Changes of the Placental Transcriptome and Infant Temperament - Buthmann, Jessica; Huang, Dennis; Casaccia, Patrizia; O’Neill, Sarah; Nomura, Yoko; Liu, Jia (Frontiers in Genetics, 2022)
Maternal stress during pregnancy exerts long-term effects on the mental well-being of the offspring. However, the long-term effect of prenatal exposure on the offspring’s mental status is only partially understood. The placenta plays a vital role in connecting the maternal side to the fetus, thereby serving as an important interface between maternal exposure and fetal development. Here, we profiled the placental transcriptome of women who were pregnant during a hurricane (Superstorm Sandy), which struck New York City in 2012. The offspring were followed longitudinally and their temperament was assessed during the first 6-12 months of age. The data identified a significant correlation between a Superstorm Sandy stress factor score and infant temperament. Further, analysis of the placental transcriptomes identified an enrichment of functional pathways related to inflammation, extracellular matrix integrity and sensory perception in the specimen from those infants with “Slow-to-Warm-up” temperament during the first year of life. Together, these findings provide initial evidence that maternal exposure to climate-related disasters results in altered placental transcriptome, which may be related to long-term emotional and behavioral consequences in children.